2016
DOI: 10.1128/jb.00622-15
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Is Dependent on the Type II Secretion System and Its Substrate LipA for Lipid Utilization and In Vivo Fitness

Abstract: Gram-negative bacteria express a number of sophisticated secretion systems to transport virulence factors across the cell envelope, including the type II secretion (T2S) system. Genes for the T2S components GspC through GspN and PilD are conserved among isolates of Acinetobacter baumannii, an increasingly common nosocomial pathogen that is developing multidrug resistance at an alarming rate. In contrast to most species, however, the T2S genes are dispersed throughout the genome rather than linked into one or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 85 publications
(74 reference statements)
2
83
0
1
Order By: Relevance
“…Specifically, mice intranasally infected with the gspD mutant strain had ϳ2-log lower bacterial burdens in both the lungs and the spleen after 36 h, compared to both the parental strain and the complemented mutant. In A. baumannii ATCC 17978, Johnson et al identified a lipase, LipA, secreted in a T2SS-dependent manner that was required for growth on medium containing lipids as a sole carbon source (72). Mutants with mutations in lipA or the T2SS structural gene gspD were less competitive than the wild-type strain in a mixed-infection murine model of bacteremia.…”
Section: Protein Secretionmentioning
confidence: 99%
“…Specifically, mice intranasally infected with the gspD mutant strain had ϳ2-log lower bacterial burdens in both the lungs and the spleen after 36 h, compared to both the parental strain and the complemented mutant. In A. baumannii ATCC 17978, Johnson et al identified a lipase, LipA, secreted in a T2SS-dependent manner that was required for growth on medium containing lipids as a sole carbon source (72). Mutants with mutations in lipA or the T2SS structural gene gspD were less competitive than the wild-type strain in a mixed-infection murine model of bacteremia.…”
Section: Protein Secretionmentioning
confidence: 99%
“…Subsequently, the T2SS of A. baumannii ATCC 17978, a commonly used laboratory strain, was shown to be active [22]. Mutagenesis of the assembly ATPase, gspE1 , or secretin, gspD , in this strain abolished secretion of a putative lipase, LipA, identifying it as a T2SS effector.…”
Section: Type II Secretionmentioning
confidence: 99%
“…Biochemical characterization of LipA showed it possessed serine hydrolase activity, capable of hydrolyzing 4-nitrophenyl myristate. LipA was required for growth in minimal media supplemented with long-chain fatty acids as the sole carbon source, indicating an important role in nutrient acquisition [22]. Furthermore, the T2SS and T2SS-dependent lipid utilization were required for competitive colonization of a neutropenic murine model of infection [22].…”
Section: Type II Secretionmentioning
confidence: 99%
See 2 more Smart Citations